The Phenomena of Glass Ceiling in Institutions Tuhapeut Gampong (Study on the Experiences of Women Reaching Top Positions in the Gampong Goverment System in Langsa City) - Maula Salsabila (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
Tuhapeut is a gampong consultative organization that has undergone several changes in terms of regional regulations and the community's point of view. The inclusion of women in the organizational structure of tuhapeut is part of a change in the identity of tuhapeut, which was previously filled only by male gampong figures. So that in terms of work practices, women are still not fully covered in several institutional policies. Even the important position of women is weakened by the existence of modernized customary law and culture in the gampong area. This research attempts to reveal the cultural constructions in the gampong that affect women's ability to obtain positions in the institution by using the glass ceiling concept. Apart from that, this research looks at the strategies used by Tuhapeut women to achieve strategic positions in the gampong government system.This research is a field research type of qualitative research using feminist ethnography research methods. Data obtained from observations, in-depth interviews, and documentation. While the theory used is the glass ceiling theory, and the theory of agency and modality of Pierre Bourdieu.The findings from this study are that there are still many performance dysfunctions faced by Tuhapeut women. The patriarchal culture that is still strong and the shari'a law that is brought in often weakens the existence of women in institutions. Nevertheless, the modality of the village women indicates that the form of women's empowerment is getting better. Such as the existence of supporting aspects of economic modality, namely social capital and cultural capital owned by Tuhapeut women. Some of these capitals form various strategies in the field, such as the family field, the religious field, and the legal and customary field.